2019
DOI: 10.3390/su11102993
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Intention to Climate Change Adaptation in Agriculture in the Red River Delta Biosphere Reserve (Vietnam): A Combination of Structural Equation Modeling (SEM) and Protection Motivation Theory (PMT)

Abstract: Coastal communities living in the low delta areas of Vietnam are increasingly vulnerable to tropical storms and related natural hazards of global climate change. Particularly in the Red River Delta Biosphere Reserve (RRDBR), farmers change the crop structure and diversify agricultural systems to adapt to the changing climate. The paper deals with a quantitative approach combined with behavior theories and surveyed data to analyze farmers’ intention to climate change adaptation in agriculture. Based on the Prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 40 publications
1
22
1
1
Order By: Relevance
“…The farmers, who perceived the major impact of climate change on agricultural production (B = 2.605; p = 0.013; OR = 13.528), or the significant efficacy of adaptation measures (B = 1.449; p = 0.071; OR = 4.261) were more likely to adapt to climate change. These findings are in line with earlier conclusions of Dang et al (2014) and Luu et al (2019) that farmers are more likely to adapt to climate change when they perceive higher risks to their farming and greater effectiveness of adaptation measures.…”
Section: Factors Affecting the Farmers' Adaptation Decisionsupporting
confidence: 92%
See 3 more Smart Citations
“…The farmers, who perceived the major impact of climate change on agricultural production (B = 2.605; p = 0.013; OR = 13.528), or the significant efficacy of adaptation measures (B = 1.449; p = 0.071; OR = 4.261) were more likely to adapt to climate change. These findings are in line with earlier conclusions of Dang et al (2014) and Luu et al (2019) that farmers are more likely to adapt to climate change when they perceive higher risks to their farming and greater effectiveness of adaptation measures.…”
Section: Factors Affecting the Farmers' Adaptation Decisionsupporting
confidence: 92%
“…Additionally, the factors related to household resources such as the number of labors, income level, nonfarm income, access to credit were also found to be associated with farmers' adaptation decisions (Deressa et al 2009;Uy et al 2015). Besides, the important role of factors related to the perception of climate change was also confirmed through its contributions to adaptation of farmers (Dang et al 2014;Luu et al 2019). The descriptive statistics of the explanatory variables are briefly described in Table 2.…”
Section: Methodsmentioning
confidence: 88%
See 2 more Smart Citations
“…Studies have found that individuals’ perceived capacity, perceived vulnerability, motivation to adapt, and other social and cognitive variables are key in understanding adaptation behaviors [ 9 , 13 , 25 , 26 ]. The ways farmers perceived their capacity to adopt new adaptation behaviors, and the risks they are exposed to have been shown to drive the adoption of new agricultural practices and pro-environmental behaviors [ 13 , 26 , 28 30 ]. While existing research demonstrates a link between climate perceptions, beliefs, and climate change adaptation amongst the general public [e.g.…”
Section: Introductionmentioning
confidence: 99%